Lung Allograft Epithelium DNA Methylation Age Is Associated With Graft Chronologic Age and Primary Graft Dysfunction - Dugger, Daniel T.; Calabrese, Daniel R.; Gao, Ying; Deiter, Fred; Tsao, Tasha; Maheshwari, Julia; Hays, Steven R.; Leard, Lorriana; Kleinhenz, Mary Ellen; Shah, Rupal; Golden, Jeff; Kukreja, Jasleen; et al. (Frontiers in Immunology, 2021)
Advanced donor age is a risk factor for poor survival following lung transplantation. However, recent work identifying epigenetic determinants of aging has shown that biologic age may not always reflect chronologic age, and that stressors can accelerate biologic aging. We hypothesized that lung allografts that experienced primary graft dysfunction (PGD), characterized by poor oxygenation in the first three post-transplant days, would have increased biologic age. We cultured airway epithelial cells isolated by transbronchial brush at one-year bronchoscopies from 13 subjects with severe PGD and 15 controls matched on age and transplant indication. We measured epigenetic age using the Horvath epigenetic clock. Linear models were used to determine the association of airway epigenetic age with chronologic ages and PGD status, adjusted for recipient PGD risk factors. Survival models assessed the association with chronic lung allograft dysfunction (CLAD) or death. Distributions of promoter methylation within pathways were compared between groups. DNA methyltransferase (DNMT) activity was quantified in airway epithelial cells under hypoxic or normoxic conditions. Airway epigenetic age appeared younger but was strongly associated with the age of the allograft (slope 0.38 per year, 95% CI 0.27–0.48). There was no correlation between epigenetic age and recipient age (P = 0.96). Epigenetic age was 6.5 years greater (95% CI 1.7 – 11.2) in subjects who had experienced PGD, and this effect remained significant after adjusting for donor and recipient characteristics (P = 0.03). Epigenetic age was not associated with CLAD-free survival risk (P = 0.11). Analysis of differential methylation of promoters of key biologic pathways revealed hypomethylation in regions related to hypoxia, inflammation, and metabolism-associated pathways. Accordingly, airway epithelial cells cultured in hypoxic conditions showed suppressed DNMT activity. While airway methylation age was primarily determined by donor chronologic age, early injury in the form of PGD was associated with increased allograft epigenetic age. These data show how PGD might suppress key promoter methylation resulting in long-term impacts on the allograft.